Determinants of Passenger Service Quality and Avsec Job Satisfaction: Analysis of Compensation, Organizational Commitment and Career Path - Ahmad, Zaini; Fikri, Muhammad; Simarmata, Juliater; Susanto, Primadi Candra (Dinasti International Journal of Management Science, 2024)
The article on determinants of passenger service quality and Avsec job satisfaction: compensation analysis, organizational commitment and career path is a scientific literature review article within the scope of human resource management science. This article aims to create a hypothesis regarding the relationship between factors, which can then be used for further research in the field of human resource management. Descriptive qualitative research methodology was used in this research. The data used in this research comes from previous research which is still relevant to the current investigation. Data was collected from leading academic online platforms, including Publish or Perish, Google Scholar, digital reference books, and Sprott journals. The findings of this research are as follows: 1) Compensation influences the quality of passenger service; 2) Organizational commitment influences the quality of passenger service; 3) Career level influences the quality of passenger service; 4) Compensation influences Avsec job satisfaction; 5) Organizational commitment influences Avsec job satisfaction; 6) Career level influences Avsec job satisfaction; and 7) The quality of passenger service influences Avsec job satisfaction.